Preparation method suitable for nano silicon dioxide sol grouting under high-temperature condition

By modifying the nano silica sol on the surface of vinyl silane and adding vinyl monomers and initiators, combining gel accelerators, an organic-inorganic hybrid gel system is formed, which solves the problems of uncontrollable gel rate and insufficient strength at high temperatures, and achieves controllable gel time and increase in strength.

CN119798569AActive Publication Date: 2025-04-11CNPC BOHAI DRILLING ENG +1

Patent Information

Application Number
CN202311312696.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-11
Publication Date
2025-04-11
Estimated Expiration
2043-10-11

AI Technical Summary

Technical Problem

The existing nano silica sol grouting materials have uncontrollable gel rate and low gel strength under high temperature conditions, which cannot meet the technical requirements for cementing the high-temperature formation.

Method used

By modifying the small-particle spherical nanosilia sol on the surface of vinyl silane, the surface of which is grafted carbon-carbon double bonds, and adding water-soluble vinyl monomers and initiators to the modified sol, and finally adding gel promoters to form an organic-inorganic hybrid gel system.

Benefits of technology

Under high temperature conditions of 70-120℃, the controllability of gel time and the increase in gel strength are achieved, solving the problems of uncontrollable gel rate and insufficient strength of grouting materials at high temperatures.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of chemical grouting materials, in particular to a preparation method suitable for nano-silica sol grouting under a high-temperature condition, and aims to solve the problems that an existing grouting material cannot be used at a high temperature, and the gel strength is low and the gel rate is uncontrollable when single silica sol is used at the high temperature. The invention provides a preparation method suitable for nano-silica sol grouting under a high-temperature condition, which comprises the following steps: step 1, carrying out surface modification on small-particle-size spherical nano-silica sol by using vinyl silane to graft carbon-carbon double bonds on the surface of the nano-silica sol to obtain modified nano-silica sol; step 2, adding a water-soluble vinyl monomer and an initiator into the modified nano silicon dioxide sol; and step 3, adding a proper amount of a gel accelerator, and enabling the system to be in an environment of 70-120 DEG C, so as to obtain the high-strength grouting material with controllable gelation time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical grouting materials, and in particular to a preparation method suitable for nano silicon dioxide sol grouting under high temperature conditions. Background Art

[0002] With the development of oil exploration and development, the advancement of drilling technology has put forward higher technical requirements for cementing. Nano silica sol is a new generation of grouting material, which has a small particle size (3-150nm) and low viscosity (usually <10mPa.S), and can easily penetrate the porous matrix of the formation, where it undergoes a physical transformation from a solid-free extrudable liquid to a highly viscous or rigid material that blocks the water layer. The curing mechanism of silica sol is very clear. Due to the electronegativity on the surface of nano silica particles, there is a diffuse double layer in the alkaline solution. Due to the existence of electrostatic repulsion, nano silica particles can be stably suspended and dispersed in alkaline solutions. Therefore, if necessary, the nano silica particles can be cross-linked with each other and form a stable three-dimensional network structure. Adding metal ions with opposite charges to the alkaline solution can neutralize the negative charge on the surface of the particles, thereby compressing the thickness of the double layer, greatly reducing the electrostatic repulsion between the particles, and prompting them to form a coherent siloxane bond (Si-O-Si) network, so that the silica sol gels and converts the liquid into a gel-like solid. Invention patent CN109305777B discloses a grouting material with silica sol as the main raw material, but does not study the use under high temperature conditions.

[0003] The formation where the underground oil well is located often reaches a high temperature of 70-120℃. Single silica sol cannot fully realize its potential when used at high temperature. There are two main disadvantages: uncontrollable gelation rate and gel strength. First of all, silica sol has a completely hydroxylated surface. When induced by other cations, covalent bonding usually occurs to produce gel. As the temperature rises, the gelation time accelerates and it cannot penetrate to the required grouting depth. The solution to this problem is usually to modify the surface of silica sol so that the Si-OH on its surface is partially replaced by other groups. However, organic coating of the surface of nano-silica particles will cause the gel strength to decrease. The reason is that the surface silane modification covers the silanol on the surface of nano-silica, reducing the bonding force between nano-silica particles. Therefore, it is necessary to find a method for preparing a high-strength nano-silica sol grouting material with controllable gelation time under high temperature conditions. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method of nano-silica sol grouting suitable for high temperature conditions, so as to solve the problems that the existing grouting materials can no longer be used at high temperatures, and the low gel strength and uncontrollable gel rate of single silica sol when used at high temperatures.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0006] A preparation method for nano-silica sol grouting suitable for high temperature conditions comprises the following steps:

[0007] Step 1: Surface modification of small-particle spherical nano-silica sol is performed with vinyl silane to graft carbon-carbon double bonds on its surface to obtain modified nano-silica sol;

[0008] Step 2: adding water-soluble vinyl monomer and initiator to the modified nano-silica sol;

[0009] Step 3: Add an appropriate amount of gel accelerator to obtain a high-strength grouting material with controllable gel time under the environment of 70-120°C.

[0010] Furthermore,

[0011] In step 1, the small-particle spherical nano-silica sol has a particle size of 5-20 nm and a solid content of 20-40%.

[0012] Furthermore,

[0013] In step 1, the vinyl silane is one or more silanes containing a vinyl group such as vinyl trimethoxy silane, vinyl triethoxy silane, etc.

[0014] Furthermore,

[0015] In step 2, the water-soluble vinyl monomer is one or more of acrylamide and hydroxymethyl acrylamide.

[0016] Furthermore,

[0017] In step 2, the amount of the water-soluble vinyl monomer used is 1-10% of the mass of the silica sol.

[0018] Furthermore,

[0019] In step 2, the initiator is one of potassium persulfate and ammonium persulfate.

[0020] Furthermore,

[0021] The amount of the initiator used is 0.3-3% of the water-soluble vinyl monomer.

[0022] Furthermore,

[0023] In step 3, the gel accelerator is one or more of potassium chloride, sodium chloride, potassium sulfate, sodium silicate, and potassium carbonate.

[0024] Furthermore,

[0025] The amount of the gel accelerator used is 0.5-5% of the mass of the silica sol.

[0026] Furthermore,

[0027] The preparation method comprises the following steps:

[0028] Step 1: Add 25g of vinyltrimethoxysilane to a mixed solvent of 80g of ethanol and 20g of water, stir and hydrolyze at room temperature for 1 hour to obtain a hydrolyzate, take 12g of the above hydrolyzate, slowly add it to 100g of silica sol with a particle size of 12nm and a solid content of 30% at a uniform speed for 120 minutes under stirring conditions, then heat it to 90°C for 1 hour to modify the surface of the nano-silica sol, and cool it to 40°C;

[0029] Step 2: Add 5 g acrylamide, 0.05 g potassium persulfate, and 20 g 10% sodium chloride aqueous solution to the product obtained in step 1, and stir to mix evenly;

[0030] Step 3: The above system is treated at 70-120°C to obtain a high-strength cured gel.

[0031] Based on the above technical solutions, the technical effects that can be achieved by the present invention are:

[0032] The present invention firstly modifies the surface of small-particle spherical nano-silica sol with vinyl silane, so that carbon-carbon double bonds are grafted on its surface to obtain modified nano-silica sol, and then adds water-soluble vinyl monomers (acrylamide, hydroxymethyl acrylamide, etc.) and initiators (potassium persulfate, ammonium persulfate, etc.) to the nano-silica sol, and finally adds an appropriate amount of gelling agent accelerator. Such a curing system will undergo two reactions under 70-120°C. The first is that vinyl monomers such as acrylamide and hydroxymethyl acrylamide will undergo free radical polymerization and copolymerize with vinyl on the surface of the nano-silica sol to form a polymer chain; the second is that sodium chloride will promote the nano-silica to produce gel, forming an inorganic network structure in which nano-silica particles are linked to each other. Under high temperature conditions, the vinyl monomer undergoes polymerization to form a polymer chain, and at the same time, the gelling agent promotes the gelation of nano-silica particles, and finally forms an organic-inorganic hybrid gel system, which can strictly control the gelation time and greatly improve its gel strength. DETAILED DESCRIPTION

[0033] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0034] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0035] Therefore, the following detailed description is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] (1) Add 25 g of vinyl trimethoxysilane to a mixed solvent of 80 g of ethanol and 20 g of water, stir and hydrolyze at room temperature for 1 hour to obtain a hydrolyzate. Take 12 g of the above hydrolyzate and slowly add it to 100 g of silica sol with a particle size of 12 nm and a solid content of 30% at a uniform speed over 120 minutes under stirring conditions, then heat it to 90°C for 1 hour to modify the surface of the nano-silica sol, and then cool it to 40°C.

[0038] (2) Add 5 g of acrylamide, 0.05 g of potassium persulfate, and 20 g of 10% sodium chloride aqueous solution to the product obtained in step (1), and stir to mix evenly.

[0039] (3) The solution in step (2) is placed in an environment of 80° C., and the gel time is observed and the gel strength is measured.

[0040] Example 2

[0041] (1) Add 25 g of vinyl trimethoxysilane to a mixed solvent of 80 g of ethanol and 20 g of water, stir and hydrolyze at room temperature for 1 hour to obtain a hydrolyzate. Take 8 g of the above hydrolyzate, slowly add it to 100 g of silica sol with a particle size of 12 nm and a solid content of 30% at a uniform speed over 120 minutes under stirring conditions, then heat it to 90°C for 1 hour to modify the surface of the nano-silica sol, and cool it to 40°C.

[0042] (2) Add 5 g of acrylamide, 0.05 g of potassium persulfate, and 20 g of 10% sodium chloride aqueous solution to the product obtained in step (1), and stir to mix evenly.

[0043] (3) The solution in step (2) is placed in an environment of 80° C., and the gel time is observed and the gel strength is measured.

[0044] Example 3

[0045] (1) Add 25 g of vinyl trimethoxysilane to a mixed solvent of 80 g of ethanol and 20 g of water, stir and hydrolyze at room temperature for 1 hour to obtain a hydrolyzate. Take 2 g of the above hydrolyzate and slowly add it to 100 g of silica sol with a particle size of 12 nm and a solid content of 30% at a uniform speed over 120 minutes under stirring conditions, then heat it to 90°C for 1 hour to modify the surface of the nano-silica sol, and then cool it to 40°C.

[0046] (2) Add 5 g of acrylamide, 0.05 g of potassium persulfate, and 20 g of 10% sodium chloride aqueous solution to the product obtained in step (1), and stir to mix evenly.

[0047] (3) The solution in step (2) is placed in an environment of 80° C., and the gel time is observed and the gel strength is measured.

[0048] Example 4

[0049] (1) Add 25 g of vinyl trimethoxysilane to a mixed solvent of 80 g of ethanol and 20 g of water, stir and hydrolyze at room temperature for 1 hour to obtain a hydrolyzate. Take 12 g of the above hydrolyzate and slowly add it to 100 g of silica sol with a particle size of 7 nm and a solid content of 20% at a uniform speed over 120 minutes under stirring conditions, then heat it to 90°C for 1 hour to modify the surface of the nano-silica sol, and then cool it to 40°C.

[0050] (2) Add 5 g of acrylamide, 0.05 g of potassium persulfate, and 20 g of 10% sodium chloride aqueous solution to the product obtained in step (1), and stir to mix evenly.

[0051] (3) The solution in step (2) is placed in an environment of 80° C., and the gel time is observed and the gel strength is measured.

[0052] Example 5

[0053] (1) Add 25 g of vinyl trimethoxysilane to a mixed solvent of 80 g of ethanol and 20 g of water, stir and hydrolyze at room temperature for 1 hour to obtain a hydrolyzate. Take 12 g of the above hydrolyzate and slowly add it to 100 g of silica sol with a particle size of 12 nm and a solid content of 30% at a uniform speed over 120 minutes under stirring conditions, then heat it to 90°C for 1 hour to modify the surface of the nano-silica sol, and then cool it to 40°C.

[0054] (2) Add 2.5 g acrylamide, 0.05 g potassium persulfate, and 20 g 10% sodium chloride aqueous solution to the product obtained in step (1), and stir to mix well.

[0055] (3) The solution in step (2) is placed in an environment of 80° C., and the gel time is observed and the gel strength is measured.

[0056] Example 6

[0057] (1) Add 25 g of vinyl trimethoxysilane to a mixed solvent of 80 g of ethanol and 20 g of water, stir and hydrolyze at room temperature for 1 hour to obtain a hydrolyzate. Take 12 g of the above hydrolyzate and slowly add it to 100 g of silica sol with a particle size of 12 nm and a solid content of 30% at a uniform speed over 120 minutes under stirring conditions, then heat it to 90°C for 1 hour to modify the surface of the nano-silica sol, and then cool it to 40°C.

[0058] (2) Add 0.5 g acrylamide, 0.05 g potassium persulfate and 20 g 10% sodium chloride aqueous solution to the product obtained in step (1), and stir to mix well.

[0059] (3) The solution in step (2) is placed in an environment of 80° C., and the gel time is observed and the gel strength is measured.

[0060] Example 7

[0061] (1) Add 25 g of vinyl triethoxysilane to a mixed solvent of 80 g of ethanol and 20 g of water, stir and hydrolyze at room temperature for 1 hour to obtain a hydrolyzate. Take 12 g of the above hydrolyzate and slowly add it to 100 g of silica sol with a particle size of 12 nm and a solid content of 30% at a uniform speed over 120 minutes under stirring conditions, then heat it to 90°C for 1 hour to modify the surface of the nano-silica sol, and then cool it to 40°C.

[0062] (2) Add 5 g of hydroxymethyl acrylamide, 0.05 g of potassium persulfate, and 20 g of 10% sodium chloride aqueous solution to the product obtained in step (1), and stir to mix evenly.

[0063] (3) The solution in step (2) is placed in an environment of 80° C., and the gel time is observed and the gel strength is measured.

[0064] Comparative Example 1

[0065] (1) 100 g of silica sol with a particle size of 12 nm and a solid content of 30% was heated to 90°C for 1 hour and then cooled to 40°C.

[0066] (2) Add 20 g of 10% sodium chloride aqueous solution to the product obtained in step (1), and stir to mix evenly.

[0067] (3) The solution in step (2) is placed in an environment of 80° C., and the gel time is observed and the gel strength is measured.

[0068] Comparative Example 2

[0069] (1) Add 25 g of vinyl trimethoxysilane to a mixed solvent of 80 g of ethanol and 20 g of water, stir and hydrolyze at room temperature for 1 hour to obtain a hydrolyzate. Take 12 g of the above hydrolyzate and slowly add it to 100 g of silica sol with a particle size of 12 nm and a solid content of 30% at a uniform speed over 120 minutes under stirring conditions, then heat it to 90°C for 1 hour to modify the surface of the nano-silica sol, and then cool it to 40°C.

[0070] (2) Add 20 g of 10% sodium chloride aqueous solution to the product obtained in step (1), and stir to mix evenly.

[0071] (3) The solution in step (2) is placed in an environment of 80° C., and the gel time is observed and the gel strength is measured.

[0072] Comparative Example 3

[0073] (1) 100 g of silica sol with a particle size of 12 nm and a solid content of 30% was heated to 90°C for 1 hour and then cooled to 40°C.

[0074] (2) Add 5 g of acrylamide, 0.05 g of potassium persulfate, and 20 g of 10% sodium chloride aqueous solution to the product obtained in step (1), and stir to mix evenly.

[0075] (3) The solution in step (2) is placed in an environment of 80° C., and the gel time is observed and the gel strength is measured.

[0076] The strength of the gel was measured using a universal material testing machine, using a cylindrical flat punch with a diameter of 12.7 mm; punching speed: 0.5 mm / s; punching depth: 20 mm; the sample was made The cylinder was pressed to 20 mm and the force required for the gel to break was recorded. The gel time of silica sol was determined by the static test tube method.

[0077] The experimental conditions and gel strengths obtained in the above various embodiments are summarized in the following table: Gel strength (N) Gel time (h) Example 1 312.56 7.5 Example 2 261.82 5.3 Example 3 157.23 0.8 Example 4 295.15 6.7 Example 5 193.77 6.8 Example 6 106.13 7.9 Example 7 195.62 9.5 Comparative Example 1 105.35 0.2 Comparative Example 2 35.62 6.5 Comparative Example 3 Produce floccules --

[0078] It can be seen from the data in the table that compared with the comparative example, the gel strength of the grouting material obtained by the preparation method provided in this embodiment is higher, and its gel time is controllable. It can be seen from Examples 1-3 that as the degree of modification of the silica sol decreases, the gel time decreases. As can be seen from Comparative Example 1, the gel time of the silica sol without any modification is only 0.2h, so the gel time can be controlled by controlling the degree of modification of the silica sol. The reason is that the silica sol has a completely hydroxylated surface, and when induced by other cations, covalent bonding usually occurs to produce a gel. The surface modification of the silica sol causes the Si-OH on its surface to be partially replaced by other groups to varying degrees, effectively improving the surface properties and reactivity.

[0079] The preparation method provided in this embodiment is easy to operate, has simple components, controllable gel time, high gel strength, and is suitable for use in high temperature environments.

[0080] In this embodiment, spherical nano-silica sol is used as the main agent. Through surface modification of vinyl silane and addition of vinyl monomer, polymerization initiator, gelling agent, etc., the vinyl monomer undergoes polymerization reaction under high temperature conditions to form a polymer chain. At the same time, the gelling agent promotes the gelation of nano-silica particles, and finally forms an organic-inorganic hybrid gel system. By controlling the degree of modification, the gelation time can be controlled, and the polymer chain formed under high temperature conditions greatly improves the gel strength.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A preparation method for nano-silica sol grouting suitable for high temperature conditions, characterized in that: The following steps are involved: Step 1: Surface modification of small-particle spherical nano-silica sol is performed with vinyl silane to graft carbon-carbon double bonds on its surface to obtain modified nano-silica sol; Step 2: adding water-soluble vinyl monomer and initiator to the modified nano-silica sol; Step 3: Add an appropriate amount of gel accelerator to obtain a high-strength grouting material with controllable gel time under the environment of 70-120°C.

2. The preparation method of nano-silica sol grouting suitable for high temperature conditions according to claim 1, characterized in that: In step 1, the small-particle spherical nano-silica sol has a particle size of 5-20 nm and a solid content of 20-40%.

3. The preparation method of nano-silica sol grouting suitable for high temperature conditions according to claim 1, characterized in that: In step 1, the vinyl silane is one or more silanes containing a vinyl group such as vinyl trimethoxy silane, vinyl triethoxy silane, etc.

4. The preparation method of nano-silica sol grouting suitable for high temperature conditions according to claim 1, characterized in that: In step 2, the water-soluble vinyl monomer is one or more of acrylamide and hydroxymethyl acrylamide.

5. The preparation method of nano-silica sol grouting suitable for high temperature conditions according to claim 1, characterized in that: In step 2, the amount of the water-soluble vinyl monomer used is 1-10% of the mass of the silica sol.

6. The preparation method of nano-silica sol grouting suitable for high temperature conditions according to claim 1, characterized in that: In step 2, the initiator is one of potassium persulfate and ammonium persulfate.

7. The preparation method of nano-silica sol grouting suitable for high temperature conditions according to claim 1, characterized in that: The amount of the initiator used is 0.3-3% of the water-soluble vinyl monomer.

8. The preparation method of nano-silica sol grouting suitable for high temperature conditions according to claim 1, characterized in that: In step 3, the gel accelerator is one or more of potassium chloride, sodium chloride, potassium sulfate, sodium silicate, and potassium carbonate.

9. The preparation method of nano-silica sol grouting suitable for high temperature conditions according to claim 1, characterized in that: The amount of the gel accelerator used is 0.5-5% of the mass of the silica sol.

10. The preparation method of nano-silica sol grouting suitable for high temperature conditions according to claim 1, characterized in that: The following steps are involved: Step 1: Add 25g of vinyltrimethoxysilane to a mixed solvent of 80g of ethanol and 20g of water, stir and hydrolyze at room temperature for 1 hour to obtain a hydrolyzate, take 12g of the above hydrolyzate, slowly add it to 100g of silica sol with a particle size of 12nm and a solid content of 30% at a uniform speed for 120 minutes under stirring conditions, then heat it to 90°C for 1 hour to modify the surface of the nano-silica sol, and cool it to 40°C; Step 2: Add 50 g acrylamide, 0.5 g potassium persulfate, and 20 g 10% sodium chloride aqueous solution to the product obtained in step 1, and stir to mix evenly; Step 3: The above system is treated at 70-120°C to obtain a high-strength cured gel.

Citation Information

Patent Citations

  • Silica sol grouting materials, their preparation methods and applications

    CN109305777B

  • Preparation method for inorganic-organic composite type profile control agent

    CN103102876A

  • Preparation method of temperature-resistant anti-salt anti-shearing nano-polymer

    CN103613723A

  • Organic inorganic nanometer composite hybrid waterproof leak stopping gel, and preparation method thereof

    CN109180870A

  • Composition and method for water and gas shut-off in subterranean formations

    CN111194344A

Cited By

  • High-durability modified acrylate grouting material and preparation method thereof

    CN121554672A

  • Highly durable modified acrylic salt grouting material and preparation method thereof

    CN121554672B